Do the Bugs in Your Gut Eat Your Memories? Relationship between Gut Microbiota and Alzheimer’s Disease - Emily M. Borsom; Keehoon Lee; Emily K. Cope (Brain Sciences, 2020)
The human microbiota is composed of trillions of microbial cells inhabiting the oral cavity, skin, gastrointestinal (GI) tract, airways, and reproductive organs. The gut microbiota is composed of dynamic communities of microorganisms that communicate bidirectionally with the brain via cytokines, neurotransmitters, hormones, and secondary metabolites, known as the gut microbiota–brain axis. The gut microbiota–brain axis is suspected to be involved in the development of neurological diseases, including Alzheimer’s disease (AD), Parkinson’s disease, and Autism Spectrum Disorder. AD is an irreversible, neurodegenerative disease of the central nervous system (CNS), characterized by amyloid-β plaques, neurofibrillary tangles, and neuroinflammation. Microglia and astrocytes, the resident immune cells of the CNS, play an integral role in AD development, as neuroinflammation is a driving factor of disease severity. The gut microbiota–brain axis is a novel target for Alzheimer’s disease therapeutics to modulate critical neuroimmune and metabolic pathways. Potential therapeutics include probiotics, prebiotics, fecal microbiota transplantation, and dietary intervention. This review summarizes our current understanding of the role of the gut microbiota–brain axis and neuroinflammation in the onset and development of Alzheimer’s disease, limitations of current research, and potential for gut microbiota–brain axis targeted therapies.